Scenario Testing For E-Business Applications.(Segue Software's LiveQuality) - Earls, Alan (InformationWeek (Manhasset, N.Y.), 1999)
Segue Software's LiveQuality provides scenarios for testing the reliability and security of electronic commerce applications. One of the scenarios mimics specific types of hacker attacks. This is the first scenario-testing application designed for e-commerce applications and to address the high-volume issues associated with service-oriented Web sites. The application offers detailed modeling and reporting of the results. It assesses three critical factors: the rate of application change, the number of transactions across multiple platforms, and the number of anticipated users. LiveQuality is a difficult application to use and Segue includes a $100,000 consulting fee in the $300,000 purchase price.